REPORT ON THE CYCLE OF OPEN LECTURES ORGANIZED BY THE RACHMISTRZ STUDENT CIRCLE (Research Bulletins of the Faculty of Economic Sciences, 2022)
On March 31 and April 14 and 21, 2021, at the Faculty of Economic Sciences of the Koszalin University of Technology, a series of open lectures was organized by the RACHMISTRZ Student Scientific Association at the Department of Finance at the Faculty of Economic Sciences of the Koszalin University of Technology. The event was supported by the Modern Business Management Program. The series of online lectures consisted of meetings on the following topics: "Don't stand, invest!", "Safe online shopping", "Cyberspace security." The lectures were conducted by representatives of the Stock Exchange School of the Stock Exchange Foundation, the Allegro.pl Security Department and Regional Director of Economic Education Programs.